2021
DOI: 10.1016/j.neuroimage.2021.118192
|View full text |Cite
|
Sign up to set email alerts
|

The impact of 1/f activity and baseline correction on the results and interpretation of time-frequency analyses of EEG/MEG data: A cautionary tale

Abstract: Typically, time-frequency analysis (TFA) of electrophysiological data is aimed at isolating narrowband signals (oscillatory activity) from broadband non-oscillatory (1/ f ) activity, so that changes in oscillatory activity resulting from experimental manipulations can be assessed. A widely used method to do this is to convert the data to the decibel (dB) scale through baseline division and log transformation. This procedure assumes that, for each frequency, sources of power (i.e., oscill… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 39 publications
1
38
0
Order By: Relevance
“…Three blocks were resting-state: one with eyes open, one with eyes closed, and one with eyes open but wearing an eye-mask to block visual input. The resting state data were used for other purposes and are reported elsewhere ( Clements et al, 2021a ; Gyurkovics et al, 2021 ). The masked data were inconclusive 1 and 2 and are not described further.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three blocks were resting-state: one with eyes open, one with eyes closed, and one with eyes open but wearing an eye-mask to block visual input. The resting state data were used for other purposes and are reported elsewhere ( Clements et al, 2021a ; Gyurkovics et al, 2021 ). The masked data were inconclusive 1 and 2 and are not described further.…”
Section: Methodsmentioning
confidence: 99%
“…Power values were baseline corrected using condition-specific subtractive baselining. We have previously shown that, compared to divisive baselining, subtractive baselining minimizes the potential of Type I errors that might occur due to the effect of the aperiodic, 1 /f component of power spectra ( Clements et al, 2021a , 2021b ; Gyurkovics et al, 2021 ). Baseline activity differs for the eyes open and eyes closed conditions, especially in the aperiodic 1/ f activity (as well as oscillatory activity), such that the eyes-closed condition has a greater 1/ f offset than the eyes-open condition ( Supp.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, nonlinear transformations should not be applied to the raw observed power before separating the contributions due to each component, because this would lead to incorrect estimation of these two parameters. For example, one of the parameters could be systematically over‐ or under‐estimated depending on the value of the other (Gyurkovics et al, 2021). Several procedures are available to achieve this separation if one is interested in applying nonlinear transformations under the narrowband+broadband model choice (Clements et al, 2021; Donoghue et al, 2020; He, 2014; Hughes et al, 2012).…”
Section: Study Planning and Data Preprocessing Stepsmentioning
confidence: 99%
“…The minimum number of trials per experimental cell observed across participants was 13. Thus, a subsample of 13 trials per experimental cell and participant was randomly selected for 1 Recent work suggests that, when non-oscillatory 1/f background "noise" differs between groups, as may be the case across age groups, dB transformation of power may distort the magnitude of the observed effects, and other baselining methods (e.g., baseline subtraction) may be preferrable (Gyurkovics, Clements, Low, Fabiani, & Gratton, 2021). However, we elected to use dB transformation for the sake of ease of interpretation and comparability with previous studies.…”
Section: Inter-trial Phase Clusteringmentioning
confidence: 99%